Elucidate or Evaluate

Geometry Level 3

arctan 1 + arctan 2 + arctan 3 = ? \large \arctan 1 + \arctan 2 + \arctan 3 = \, ? Bonus Prove without using trigonometrical identifies

2 π \pi π / 2 \pi/2 0 π \pi - π \pi

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Θ = arctan 1 + arctan 2 + arctan 3 = arctan ( 1 + 2 1 2 ) + arctan 3 = arctan ( 3 ) + arctan 3 = arctan ( 3 + 3 1 + 9 ) = arctan 0 Since 0 < Θ < 3 π 2 = π \begin{aligned} \Theta & = \arctan 1 + \arctan 2 + \arctan 3 \\ & = \arctan \left(\frac {1+2}{1-2} \right) + \arctan 3 \\ & = \arctan \left(-3\right) + \arctan 3 \\ & = \arctan \left(\frac {-3+3}{1+9} \right) \\ & = \arctan 0 & \small {\color{#3D99F6}\text{Since } 0 < \Theta < \frac {3\pi}2} \\ & = \boxed{\pi} \end{aligned}

Prajwal Krishna
Nov 4, 2016

Let
z 1 { z }_{ 1 } =1+i
z 2 { z }_{ 2 } =1+2i
z 3 { z }_{ 3 } =1+3i


Therefore

z 1 { z }_{ 1 } = r 1 { r }_{ 1 } e arctan 1 { e }^{ \arctan { 1 } }

z 2 { z }_{ 2 } = r 2 { r }_{ 2 } e arctan 2 { e }^{ \arctan { 2 } }

z 3 { z }_{ 3 } = r 3 { r }_{ 3 } e arctan 3 { e }^{ \arctan { 3 } }

(1+i)(1+2i)(1+3i)=1+6i-11-6i

\Rightarrow z 1 { z }_{ 1 } × \times z 2 { z }_{ 2 } × \times z 3 { z }_{ 3 } = -10 \Rightarrow argument of[ z 1 { z }_{ 1 } × \times z 2 { z }_{ 2 } × \times z 3 { z }_{ 3 } ]=argument of (-10)

\Rightarrow arctan 1 \arctan { 1 } + arctan 2 \arctan { 2 } + arctan 3 \arctan { 3 } = π \pi

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...